Fiscal Policies for Development and Climate Action - Pigato, Miria A. (Washington, DC: World Bank, 2018)
Fiscal policies can lay the foundation for low-carbon and climate-resilient development. Building on more than two decades of research in development and environmental economics, this book argues that fiscal instruments are crucial for mitigating and adapting to climate change while raising human welfare. By implementing environmental tax reforms, developing countries can reap a “triple dividend”: cutting pollution, raising economic activity, and generating development cobenefits, such as cleaner water, safer roads, and improvements in human health. These reforms need not harm competitiveness. Empirical evidence, including from Indonesia and Mexico, suggests that raising fuel prices can increase firm productivity. In addition, risk management strategies are needed to bolster economic resilience to climate-induced natural disasters. Modelling suggests that preventive public investments and measures to build fiscal buffers can help safeguard stability and growth in the face of rising climate risks. In this way, environmental tax reforms and climate risk-management strategies can lay the much-needed fiscal foundation for development and climate action.